Psychometric properties and reliability of the Brazilian version of Parent Attitudes about Childhood Vaccine (PACV-BR) - Claudio José dos Santos Júnior; Maria Rosa da Silva; Paulo José Medeiros de Souza Costa (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: To evaluate the psychometric properties and reliability of the Brazilian version of the tool Parent Attitudes about Childhood Vaccine (PACV-BR). Methods: The sample included 110 parents of children up to two years old served by Family Health Basic Units. The tool's internal consistency and factor validity were respectively assessed by Cronbach's alpha and exploratory factor analysis (EFA). The test-retest reliability was assessed by the intraclass correlation coefficient (ICC). Results: The EFA results indicated a proper structural adequacy of the PACV-BR (15 items and two factors). The reliability generated Cronbach's alpha values between 0.715 and 0.854 for the items, of 0.918 for the tool as a whole, of 0.877 for factor 1 and of 0.825 for factor 2, in addition to an ICC of 0.984. Conclusions: The PACV-BR showed evidence of construct validity and reliability.